Differential effects of nanoselenium doping on healthy and cancerous osteoblasts in coculture on titanium - Phong A Tran (Dove Medical Press, 2010)
Phong A Tran1, Love Sarin2, Robert H Hurt2, Thomas J Webster2,31Physics Department,2Division of Engineering,3Department of Orthopedic Surgery, Brown University, Providence, RI, USAAbstract: In the present study, selenium (Se) nanoclusters were grown through heterogeneous nucleation on titanium (Ti) surfaces, a common orthopedic implant material. Normal healthy osteoblasts (bone-forming cells) and cancerous osteoblasts (osteosarcoma) were cultured on the Se-doped surfaces having three different coating densities. For the first time, it is shown that substrates with Se nanoclusters promote normal osteoblast proliferation and inhibit cancerous osteoblast growth in both separate (mono-culture) and coculture experiment. This study suggests that Se surface nanoclusters can be properly engineered to inhibit bone cancer growth while simultaneously promoting the growth of normal bone tissue.Keywords: selenium, coating, nanotechnology, biomaterials, orthopedics, bone cancer